Utilization of Village Funds for Community Development in Murung Raya Village, South Banjarmasin District - Rukman, Rukman (AKTIVA: Journal of Accountancy and Management, 2025)
Purpose: The Village Fund is a government program in supporting and realizing developments in the village. The purpose of this study is to find out the utilization of Village Funds (DK) in Murung Raya Village, South Banjarmasin District. As well as the fulfillment of the principles of village development in the Utilization of Village Funds. Design/methodology/approach: The research uses a qualitative descriptive approach. In this study, the subjects of the study are the Head of the Village, Secretary, Treasurer, Head of Development and the community. Data collection is based on the results of observations, interviews and documentation studies. Data analysis uses the Miles & Huberman approach.Research Findings: The result of this study is that the use of Village Funds in supporting the development of Murung Raya Village Infrastructure has been effective. This can be proven by the number of development programs that have been realized in accordance with the development plan. The involvement of the community in the utilization of village funds is quite good, this is one of the expectations that are desired for the community. The community has been involved in the preparation of the plan and is directly involved in the development work even to the development stage of the program. Theoretical Contribution/Originality: This research contributes to the Murung Raya Village government to further mature development planning in the Village and empower the local community. Tujuan Penelitian: Dana Desa merupakan program pemerintah dalam mendukung dan mewujudkan pembangunan di desa. Tujuan dari penelitian ini adalah untuk mengetahui pemanfaatan Dana Desa (DK) di Desa Murung Raya, Kecamatan Banjarmasin Selatan, serta pemenuhan prinsip-prinsip pembangunan desa dalam pemanfaatan Dana Desa. Desain/Metodologi/Pendekatan: Penelitian ini menggunakan pendekatan deskriptif kualitatif. Subjek penelitian dalam studi ini meliputi Kepala Desa, Sekretaris, Bendahara, Kepala Pembangunan, dan masyarakat. Pengumpulan data dilakukan melalui observasi, wawancara, dan studi dokumentasi. Analisis data menggunakan pendekatan Miles & Huberman. Temuan Penelitian: Hasil penelitian menunjukkan bahwa pemanfaatan Dana Desa dalam mendukung pembangunan infrastruktur Desa Murung Raya telah efektif. Hal ini dapat dibuktikan dengan banyaknya program pembangunan yang telah terealisasi sesuai dengan rencana pembangunan. Keterlibatan masyarakat dalam pemanfaatan Dana Desa cukup baik, yang merupakan salah satu harapan yang diinginkan dari masyarakat. Masyarakat telah dilibatkan dalam penyusunan rencana serta terlibat langsung dalam pekerjaan pembangunan hingga tahap pengembangan program. Kontribusi Teoretis/Orisinalitas: Penelitian ini berkontribusi bagi pemerintah Desa Murung Raya dalam memperkuat perencanaan pembangunan desa serta memberdayakan masyarakat lokal.